East Asian economies: trends in saving and investment - Rao, Bhanoji (2001)
This essay deals with the saving and investment trends in the east Asian economies. They generated high rates of saving and used the resources productively. The high rates of saving reflect high rates of both private saving and public sector saving. The high investment rate was not only due to high saving rate, but also a relatively high level of inflow of foreign direct investment in some, backed by the policy of openness to trade and investment. - Reproduced
Keywords: Investment - East Asia; Savings - East Asia; Savings